The Birth of American Phenomenology in Josiah Royce's "New Phenomenology": Reflections on the 1878-1880 Thought Diary in Dialogue with the Philosophy of Contemplative Practice in Husserlian Phenomenology and Peircean Pragmatism (Nóema, 2022)
This article explores the birth of American Phenomenology in Josiah Royce’s “New Phenomenology”, proposed in his Thought Diary (1878-1880), in dialogue both with Husserl’s Contemplative Practice and with Peirce’s version of pragmatism.
Keywords: Phenomenology; Pragmatism; Royce; Husserl; Peirce